Cognitive Development One Year After Infantile Critical Pertussis*. Issue 2 (February 2018) - Berger, John T.; Villalobos, Michele E.; Clark, Amy E.; Holubkov, Richard; Pollack, Murray M.; Berg, Robert A.; Carcillo, Joseph A.; Dalton, Heidi; Harrison, Rick; Meert, Kathleen L.; Newth, Christopher J. L.; Shanley, Thomas P.; et al.
Abstract : Objectives: Pertussis can cause life-threatening illness in infants. Data regarding neurodevelopment after pertussis remain scant. The aim of this study was to assess cognitive development of infants with critical pertussis 1 year after PICU discharge. Design: Prospective cohort study. Setting: Eight hospitals comprising the Eunice Kennedy Shriver National Institute for Child Health and Human Development Collaborative Pediatric Critical Care Research Network and 18 additional sites across the United States. Patients: Eligible patients had laboratory confirmation of pertussis infection, were less than 1 year old, and were admitted to the PICU for at least 24 hours. Interventions: The Mullen Scales of Early Learning was administered at a 1-year follow-up visit. Functional status was determined by examination and parental interview. Measurements and Main Results: Of 196 eligible patients, 111 (57%) completed the Mullen Scales of Early Learning. The mean scores for visual reception, receptive language, and expressive language domains were significantly lower than the norms ( p < 0.001), but not fine and gross motor domains. Forty-one patients (37%) had abnormal scores in at least one domain and 10 (9%) had an Early Learning Composite score 2 or more SDs below the population norms. Older age ( p < 0.003) and Hispanic ethnicity ( p < 0.008) were associated with lower mean Early Learning Composite score, but presenting symptoms and PICU course were not. Conclusions: Infants who survive critical pertussis often have neurodevelopmental deficits. These infants may benefit from routine neurodevelopmental screening.